A Popular Buddhist Story at the Ming Court of the Early Sixteenth Century: Images of Miaoshan in the Monastery of the Great Wisdom in Beijing and Precious Scroll of Incense Mountain*. (2nd January 2017) - Berezkin, Rostislav
Abstract : This paper analyzes early illustrations of the Miaoshan story, which served a popular hagiography of Bodhisattva Guanyin — the murals of the Hall of the Great Mercy of the Monastery of Great Wisdom in Beijing (ca. 1513) — in relation to the vernacular narrative of performative nature, the Precious Scroll of Incense Mountain . These murals, though they have not received much attention from scholars so far, are noteworthy as the whole ensemble of this monastery was commissioned by Zhang Xiong, a powerful eunuch of the Zhengde court. This paper clarifies the source of the subject of these murals with the use of newly discovered textual materials, and also tries to contextualize them in the cultural life of eunuchs. Such analysis also leads to redefining the status of precious scroll literature, which, though written in vernacular language, was also used in the higher stratum of society, and entered the Ming inner court in the fifteenth to early sixteenth centuries.